(untitled) (Research, Society and Development, 2021)
Introduction: The management of calcified canals is a challenge during endodontic treatment, which is why clinical alternatives have been sought to improve their approach. One of them, recently introduced, is the use of guided procedures, which are considered safe and accurate when locating calcified canals, thus reducing the risk of operative errors and benefiting the success of endodontic therapy. Materials and methods: This review of the literature is of a qualitative nature that aimed to analyze the available scientific evidence regarding the use of guided endodontics to treat teeth with calcified root canals. To this end, a search was carried out in the PubMed databases. , Cochrane Library and Journal of Endodontics for corresponding data extraction. Conclusions: Guided endodontics is considered a precise method to approach teeth with calcified root canals, generating favorable expectations in the clinical environment, this procedure can be performed through static guides or dynamic guides obtaining good results, such as: performing conservative, straight-line access cavities, minimally invasive preparations, shorter operative time, and decreased clinical procedure errors.